Long-term MBR performance of polymeric membrane modified with Bismuth-BAL chelate (BisBAL). Issue 15 (3rd July 2019) - Turken, Turker; Kose-Mutlu, Borte; Okatan, Selin; Durmaz, Gamze; Guclu, Mehmet C.; Guclu, Serkan; Ovez, Suleyman; Koyuncu, Ismail
ABSTRACT: An ultrafiltration membrane prepared by polyethersulfone (PES) was modified with Bismuth-BAL chelate (BisBAL) and was used in submerged membrane bioreactor system. Moreover, a control membrane reactor was also tasked to evaluate the effect of BisBAL on the membrane performance. The flux profile, transmembrane pressure, the effect of chemical treatment, cake layer formation, anti-fouling properties against extracellular polymeric substances (EPS) and soluble microbial products (SMP) were studied. The UF modified membrane demonstrated a sustained permeability, low cleaning frequency, and longer filtration time. In terms of anti-EPS and SMP accumulation, the modified membrane showed a lower membrane resistance. It can be illustrated from scanning electron microscopy and confocal laser scanning microscope images that the modified membrane had presented better properties than bare PES membrane, as it was looser and thinner. Thus, the UF membrane proved to be more efficient in terms of permeability and lifetime.